PHYTOCHEMICALS &ANTIMICROBIAL ACTIVITY OF LEAVES OF HOMONOIA RIPARIA L. - RAHUL SHIVAJI PATIL,; ASHVIN G. GODGHATE,; RAJARAM S. SAWANT, (International Journal of Pharma and Bio Sciences, 2014)
Present study deals with the qualitative phytochemical and antimicrobial activity of leaves of Homonoia ripariaLour using various extracts (Aqueous, Ethyl Acetate, nHexane). Aqueous extract contains more number of secondary metabolites whereas ethyl acetate extract contains a least number. Antimicrobial activity of Homonoia riparia leaf extract was tested against Proteus vulgaris, Staphylococcus aureus, Salmonella typhimurium; Bacillus cereus by agar well diffusion methods. The n-hexane extracts does not show inhibition against any organism while ethyl acetate extract shows a significant range of inhibitory effect against Proteus vulgaris, Salmonella typhimurium, Bacillus cereus.